The effect of dispersion mechanisms on aroma delivery - Pearson, Kris S.K. (2005)
Dispersion of aroma compounds in food matrices is a common process in the production of many food products. However, the degrees of dispersion on the distribution and subsequent release of these compounds during consumption may have considerable consequences for perception of these flavours.